Black Hole detection and avoidance in mobile Adhoc Networks (International Journal of Engineering and Computer Science, 2015)
The paper evolved out to address issues in MANET like security and performance. This paper proposes a cluster based concept to improve security and efficiency and guarantees the optimum utilization of the network resources. Performance proposed of MANET in presence of black hole attack. The simulation of the proposed methodology is carried out using NS2 network simulator and the simulation results reflects the performance of scheme for detection and prevention of the black hole.